Effect of Sweet Potato (Ipomoea batatas) Tuber on Sperm Profile and Testicular Integrity of Male Albino Rats - , P. B. Ekpo; , U. U. Uno; , H. O. Ogbe; , U. B. Ekaluo (Archives of Current Research International, 2017)
Aim: Globally, plant parts have been used for several purposes such as medicinal additives and food supplement. This is not unconnected to the fact that one or more parts of almost all plants contain active ingredients with medicinal and therapeutic properties. Hence, the study was conducted to determine the effect of sweet potato (Ipomoea batatas) tuber extract on the weight of testes and epididymes, epididymal sperm count, motility, viability, semen pH, sperm head abnormality and histology of testes in albino rat models. Place and Duration of the Study: This study was carried out in the Animal house of the Department of Genetics and Biotechnology, University of Calabar, Calabar and lasted for 65 days. Methodology: Twenty four male rats were randomly divided into four groups of six rats each using a completely randomized design. Group A served as control and received only water and pellet feed while group B, C and D received 200 mg/kg, 400 mg/kg and 600 mg/kg body weight of the aqueous extract ofIpomoea batatas tuber, respectively. Results: Results obtained revealed that the tuber extract did not significantly affect the weight of epididymes, sperm motility, sperm viability, sperm count, sperm head abnormalities and testicular integrity in the extract – treated animals when compared to the control group. No significant differences were also observed in semen pH and weight of testes (computed P value for weight of testes, weight of epididymes, sperm count, sperm motility, viability, semen pH and sperm head abnormality were 2.08, 1.89, 2.97, 2.63, 1.54, 2.30 and 1.08, respectively while the critical P value = 3.072 at 5% level of significance). Conclusion: The findings of the study suggest that aqueous extract of I. batatas tuber does not have toxic effect on the sperm profile and testicular integrity of male albino rats.